Pengembangan Website Desa Dalam Meningkatkan Kualitas Pelayanan Publik di Desa Bona, Gianyar - Gusti Ayu Dwi Intan Mahayoni; I Dewa Ayu Putri Wirantari (Program Studi Administrasi Negara, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Warmadewa, 2021)
The poor quality of public services in Indonesia must be addressed by the government. One of the government's efforts to improve the quality of public services is to take advantage of advances in information technology in the process of governance. This is known as e-government or electronic or internet-based government administration. The process of implementing e-government goes through several stages, namely presence (web presence), interaction (interaction), transactions (transactions), and transformation (transformation). This study aims to determine how the implementation of e-government through the provision and operation of village websites can improve the quality of public services in Bona Village. This research is a qualitative-descriptive type of research that describes and explains the results of research based on relevant data collected through observation and literature study. The analysis of the research data used the Miles and Huberman model which included the initial data collection stage, the data reduction stage, the data presentation stage, and then the conclusion drawing stage. The results of this study are the application of e-government is carried out through the provision and operation of village websites as a means of public services that are easy, practical, and efficient. There are several services related to village administration including writing business letters, complaint reports, writing letters for other purposes, and essential telephone services. These services can be accessed by the village community easily and through a mechanism or procedure that is not complicated, so that the community feels satisfied with the public services they get. Based on the research results, it can be concluded that the application of e-government through the provision and operation of village websites that provide easy and practical public services can improve the quality of public services in Bona Village. Through the application of e-government, the implementation of village government can be carried out effectively, efficiently, transparently and accountably.